2020
DOI: 10.1093/mnras/staa2568
|View full text |Cite
|
Sign up to set email alerts
|

Box/peanut-shaped bulges in action space

Abstract: We introduce the study of box/peanut (B/P) bulges in the action space of the initial axisymmetric system. We explore where populations with different actions end up once a bar forms and a B/P bulge develops. We find that the density bimodality due to the B/P bulge (the X-shape) is better traced by populations with low radial, $\rm J_{R,0}$, or vertical, $\rm J_{z,0}$, actions, or high azimuthal action, $\rm J_{\phi ,0}$. Generally populations separated by $\rm J_{R,0}$ have a greater variation in bar strength … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 99 publications
0
36
1
Order By: Relevance
“…However the single chemical track of the bulge implies that separating populations by the α−abundance is similar to separating by metallicity. In summary, these observational results point to stronger barred streaming motions in metal-rich stars, which is borne out by models and simulations (Portail et al 2017;Debattista et al 2020). However the origin of each component within the bulge is still a matter of debate.…”
Section: Kinematic Differences Between Different Populations In the Milkymentioning
confidence: 76%
See 2 more Smart Citations
“…However the single chemical track of the bulge implies that separating populations by the α−abundance is similar to separating by metallicity. In summary, these observational results point to stronger barred streaming motions in metal-rich stars, which is borne out by models and simulations (Portail et al 2017;Debattista et al 2020). However the origin of each component within the bulge is still a matter of debate.…”
Section: Kinematic Differences Between Different Populations In the Milkymentioning
confidence: 76%
“…This led Di Matteo et al (2019) to argue that, in addition to the radial velocity dispersions, the vertical dispersion also played a key role in the vertical thickening of populations. However, Debattista et al (2020) showed vertical thickening is a monotonic function of the initial radial action of a given stellar population. Consequently, a thick disc can produce a vertical gradient largely because it has a higher radial velocity dispersion.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In summary, these observational results point to stronger barred streaming motions in metal-rich stars, which is borne out by models and simulations (Portail et al 2017;Debattista et al 2020). However, the origin of each component within the bulge is still a matter of debate.…”
Section: Discussionmentioning
confidence: 55%
“…Appendix C Alternate Metallicity Assignment Debattista et al (2020) found, in the context of the Galactic bulge that metallicities assigned to star particles in simulations are more accurate when painted on according to initial axisymmetric action. Figure 12 shows our proposed signatures when metallicities are assigned according to (2020) (left column).…”
Section: Appendix B Axisymmetric Approximate Actions Calculated With ...mentioning
confidence: 99%